Duas novas espécies de Neocordulia Selys, 1882 do sul do Brasil (Anisoptera: Corduliidae) (Lundiana: International Journal of Biodiversity, 2008)
Two new species of Neocordulia Selys, 1882 — N. fiorentini sp. n. and N. gaucha sp. n. — both from Rio Grande do Sul, Brazil, are described and illustrated. They differ from other species of the genus mainly by the shape of anal appendages, sternal protuberance of abdominal segment 8 and sternum of abdominal segment 9.